Idiomaticity in ESL contexts: appropriacy versus conformity - Chidimma U.E.Inyima; Mary Ngozi Nwodo; Henry Obumneme Okoro; Chinedu Nwadike; Simeon Nwabueze Osogu (Penerbit Universiti Kebangsaan Malaysia, 2024)
Studies on the domestication of idioms in English as second language contexts have investigated the strategies of domestication and the cultural imperatives of the innovative or else deviant usages as well as the implications for pedagogy, standardization and international intelligibility of the usages. Differing from earlier studies, this paper investigates idiomatic adaptation in Chimamanda Adichie’s novels with the objective of establishing their causes, discourse-pragmatic functions and stylistic import. The data consist of sixty-one (61) instances of idiomatic adaptation identified through a close reading of Adichie’s three novels: Purple Hibiscus (2003), Half of a Yellow Sun (2006) and Americanah (2013). The data were analyzed using a synthesis of insights from a discourse-pragmatic and functionalist approach with a focus on contexts of culture and situation. The findings reveal that idiomatic adaptations in ESL contexts are borne out of pragmatic constraints, the need for contextual and cultural appropriacy, communicative effectiveness and a bias for social function over grammaticality. The adaptations include both translated indigenous idioms and domesticated Standard British idioms. The translated indigenous idioms function especially as palliation, omen, and emphasis pragmatic markers, and the domesticated Standard British English idioms especially as emphasis pragmatic markers. Contextual appropriacy was realized by means of translated indigenous idioms and cultural appropriacy via indigenized Standard British English idioms through the evocation of commonplace culture-bound images, symbols and shared knowledge. Communicative effectiveness was achieved by the pairing of linguistic form and appropriate context. The idiomatic adaptations as such have a functional significance especially as Adichie’s novels present a higher incidence of translated indigenous idioms than domesticated Standard British English idioms.